Antitumoral activity of Ficus carica L. on colorectal cancer cell lines - Soltana, Hala; Pinon, Aline; Limami, Youness; Zaid, Younes; Khalki, Loubna; Zaid, Nabil; Salah, Driss; Sabitaliyevich, Uteuliyev Yerzhan; Simon, Alain; Liagre, Bertrand; Hammami, Mohamed (Cellular and Molecular Biology, 2019)
In traditional medicine, Ficus carica (also known as fig) latex is recognized as a remedy with various therapeutic effects. In the present study we investigated the antitumor activity of Ficus carica extracts and latex. We evaluated the effects of increasing concentrations of Ficus carica extracts and latex on HCT-116 and HT-29 human colorectal cell proliferation using MTT assay and apoptosis induction by evaluating PARP cleavage by Western blot analysis. Peel, pulp, leaves, whole fruit and latex extracts of Ficus carica exerted significant antiproliferative effects on HCT-116 (IC50 values 239, 343, 177, 299, 206 µg/ml) and HT-29 cells (IC50 values 207, 249, 230, 261, 182 µg/ml) after 48h of treatment. Furthermore, treatment with different extracts of Ficus carica induced apoptosis in both HT-29 and HCT-116 cancer cells. Leaves and latex extracts of Ficus carica showed the strongest antiproliferative activities. Overall, our results showed that these natural products are strong apoptosis inducers which suggest their use of for therapeutic purposes.